Experience in the emergency cardiology department in wartime conditions. (3rd May 2023) - Lutay, I; Parkhomenko, A; Irkin, O; Skarzhevskyi, O; Shumakov, O; Bilyi, D; Stepura, A; Khomiakov, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Physical and psycho-emotional stress during the war can provoke an aggravation of cardiovascular pathology and contribute to the development of in-hospital complications. The aim of our work was to analyze pts admitted to emergency cardiology department in our city during the first months (from February 24 to May 31, 2022) of 2022 russian full-scale invasion of Ukraine and compared their clinical characteristics and the course of in-hospital period with patients hospitalized during the same period of 2019 (pre COVID-19 era). The total number of pts hospitalized in 2022 was half as much as in 2019 (98 pts vs. 202 pts), which can be partly explained by civilian migration and mobilization. The average age of patients (62.8±12.7 yo in 2019 vs 64.8±13.6 yo in 2022, p>0.05) and the number of women (27.2% vs 33.7%, p>0.05) did not change. There were no changes in main causes of hospitalizations: ACS (58.9% in 2019 vs 61.2% in 2022, p>0.05), ADHF (22.8% vs 18.4%, p>0.05), hypertensive urgencies (10.9% vs 14.3%, p>0.05), arrhythmias (4.4% vs 6.2%, p>0.05). 98 pts and 49 patients with STEMI were treated during studied periods of 2019 and 2022, accordingly. There were no significant differences in the main clinical characteristics between groups. The GRACE score in groups was almost the same (154.3±33.0 pts vs 160.8±43.5 pts, p=0.366). Cardiogenic shock at admission was diagnosed in slightly less than 10% of pts, Killip II or III in about 20% of pts with no difference between groups. Despite the absence of a significant difference in the level of arterial pressure, heart rate at admission was 10 bpm more during the wartime (84, 0±15, 4 bpm vs 74, 9±20, 6 bpm, p=0.005). 88.7% of STEMI pts in 2019 and 75.5% of pts in 2022 (p=0.064) were admitted during the first 24 hrs after symptoms onset. The mean time to hospitalization in this pts was 4.4±3.8 hrs in 2019 and 6.4±5.6 hrs this year (p=0.044). This time delay led to a lower number of pPCI made during the wartime (82.5% vs. 59.2%, p=0.005), despite the same total number of angio (90.7% in 2019 vs. 91.5% in 2022, p=0.821) and PCI (86.6% in 2019 vs. 79.6% in 2022=0.304). No-reflow (TIMI<3 or MBG<2) was registered in 34.3% of pts this year and 12.9% in 2019, p=0.039. There were no differences in medical treatment between groups. In-hospital mortality in STEMI pts in wartime period was two times higher (but not significant) than in 2019 (4.9% in 2019 vs 10.2% in 2022, p=0.302). Patients with STEMI hospitalized during the first three months of the war had significantly higher rate of ventricular fibrillations (4.3% in 2019 vs 15.3% in 2019, p=0.043). During the first months of hostilities, the structure of hospitalization in the emergency cardiology department did not change. Patients with STEMI were hospitalized later and had a greater number of in-hospital complications.